Ascochyta bombacina sp. nov. causing leaf blight of Bombax ceiba and its management - and M. BASU, ARUSHI MEHROTRA, M.D. MEHROTRA (Indian Phytopathology, 2004)
Leaf blight, a new disease of Bombax ceiba caused by Ascochyta bombacina sp. nov., was recorded from New Forest, Dehra Dun. The disease, occurred in the nursery as well as in the young plantations. The disease incidence in the nursery was 100% whereas it was 80% in the plantation. However, the disease was highly destructive in the nursery causing 40-85% defoliation. On the other hand, the disease in the plantation was poor to moderate and in majority of the plants defoliation was less than 15%. Fall in temperature in October and its further lowering in November, shade to the plants by the adjoining tree plantations and wetting of leaf surface by dew were crucial for disease development in severe form. The disease in the nursery was controlled effectively by foliar application of Topsin (0.1%).